Public audit and ways to enhance the activities of the revision group in the republic of Kazakhstan - TUZUBEKOVA M.; KONYRBEKOV M.; BIKTEUBAYEVA A.; KOBIYEVA A.; TLEUBAYEVA S.; PRALIEVA S. (The journal of contemporary issues in business and government, 2020)
Abstract: The analysis of activity of revision group in the system of public audit in regions of the Republic of Kazakhstan in modern conditions has been carried out in this article. The issues of effective management of budget funds and reinforcement of financial and executive discipline, as well as the importance and necessity of carrying out joint or parallel control activities by external state control bodies have been studied. The author has studied the issues of efficiency of using budget funds and control activities.